The Role of Antioxidants in Inflammatory Immune Response: Evaluating Fruit and Vegetable Consumption for NCD Prevention in Nabire, 2025 - Reza Fahrepi; Anto J Hadi; Yusuf Efendi (Lembaga Pengembangan Kinerja Dosen, 2025)
Non-communicable diseases (NCDs) remain a leading cause of global morbidity and mortality, with chronic inflammation as a key pathophysiological mechanism. Antioxidants from fruits and vegetables have demonstrated potential to modulate inflammatory immune responses, thus contributing to NCD prevention. This study aimed to evaluate the effectiveness of fruit and vegetable consumption promotion policies in preventing NCDs by modulating inflammatory immune responses in Nabire District in 2025. The research employed a mixed-methods design, incorporating both quantitative and qualitative data from 384 adult respondents. Data were gathered through food consumption surveys, inflammatory biomarker analysis (CRP, IL-6, TNF-α), and an evaluation of policy implementation. Descriptive and inferential analyses were conducted using SPSS 28.0 and R version 4.3.0. Results revealed that average fruit and vegetable consumption in Nabire residents remained below the WHO recommended intake (289g/day vs. 400g/day), although there was a noticeable improvement compared to previous years. A significant negative correlation was found between antioxidant intake and inflammatory biomarkers (r=-0.478, p<0.001). Policy implementation reached 74% coverage with a 62% compliance rate, indicating significant improvements in reach compared to prior assessments. The study concludes that fruit and vegetable consumption promotion policies show enhanced potential in modulating inflammatory immune responses for NCD prevention. However, continued efforts in strengthening policy implementation and adopting innovative monitoring strategies, particularly through digital health technologies, are essential for achieving sustained impact